PENELITIAN DAN PENGEMBANGAN SITUS PERMUKIMAN LINGKUNGAN DANAU DI JAWA TIMUR: SATU UPAYA MENJALIN KEMITRAAN DALAM PENGELOLAAN SUMBERDAYA ARKEOLOGI - Gunadi Kasnowihardjo (Berkala Arkeologi, 2007)
Archaeologists' foresight in handling the results of their research will determine the impact that will be felt by the wider community. This is what some of our archaeologists have not thought about. Most archaeological research results end in Archaeological Research Reports or Archaeological Research News which are only limited to reading by archaeological observers, including students majoring in Archeology or history who need for academic purposes. By trying to establish partnerships and cooperation with various sectors and interests, hopefully the reach, thoughts and considerations in determining the archaeological research model will be more extensive and more grounded.